Jawabanmu

2014-03-24T08:46:29+07:00
F(x) = ax + b             f(x) = ax +b 
f(1) = 1a + b              f(4) = 4a + b
-1 = 1a + b                5 = 4a + b

dieliminasi
a + b = -1
4a + b = 5
dikurangkan, jadi
-3a = -6
a = 2

a + b = -1
2 + b = -1
     b = -3

b) f (x) = ax + b
    f(x) = 2x - 3
    f(6) = 2.6 - 3
          = 12 - 3
          = 9

c) f(c) = ac + b
    17 = 2c - 3
    2c = 20
      c = 10
1 3 1
2014-03-24T09:57:00+07:00
a. Nilai a dan b
∞ f(1) = -1
f(x) = ax + b             
f(1) = 1a + b            
  -1 = a + b            

∞ f(4) = 5
f(x) = ax + b
f(4) = 4a + b
   5 = 4a + b

Gunakan Cara Eliminasi
  a + b = -1
4a + b = 5   
     -3a = -6
        a = 2

Kemudian Gunakan Cara Subtitusi
a + b = -1
2 + b = -1
      b = -3

b. Nilai f(6)
f(x) = ax + b
f(x) = 2x - 3
f(6) = 2.6 - 3
f(6) = 12 - 3
f(6) = 9

c.
Jika f(c) = 17 ,maka hitunglah nilai c
f(x) = ax + b
f(c) = ac + b
 17 = 2c - 3
 2c = 20
   c = 10